Molecular epidemiology and genotype-specific disease severity of hepatitis E virus infections in Germany, 2010–2019. Issue 1 (31st December 2022) - Schemmerer, Mathias; Wenzel, Jürgen J.; Stark, Klaus; Faber, Mirko
ABSTRACT: Zoonotic hepatitis E virus (HEV) is endemic in Europe. Genotype 3 (HEV-3) is predominant but information on subtype distribution, trends and clinical implications in Germany is scarce. We analysed 936 HEV RNA positive samples of human origin and corresponding national surveillance data from 2010 to 2019. Samples were referred to the National Consultant Laboratory and sequenced in at least one of four genomic regions. Sequences were analysed using bioinformatics methods and compared to the latest HEV reference set. 1, 656 sequences were obtained from 300 female, 611 male and 25 of unknown sex aged 3–92 years (median 55 years). HEV-3c was predominant (67.3%) followed by HEV-3f, HEV-3e and HEV-3i(-like) with 14.3%, 9.7% and 4.0% (other subtypes ≤1.1%). The proportion of HEV-3 group 2 (3abchijklm) strains increased over time. Jaundice, upper abdominal pain, fever, hospitalization, and death due to HEV were significantly more often reported for patients infected with HEV-3 group 1 (3efg) compared to group 2. Larger spatio-temporal clusters of identical sequences were not observed. HEV-3 group 1 infections are more severe as compared to the predominant group 2. Detection of group 2 strains increased over the last years, possibly due to more frequent diagnosis of asymptomatic and mild courses. The diversity of strains and the space–time distribution is compatible with a foodborne zoonosis with supra-regional distribution of the infection vehicle (pork products). GRAPHICAL ABSTRACT: UF0001